Glomus tumors with malignant features of the extremities: a case series - Wood, Taylor R. (Clin Sarcoma Res, 2020)
BACKGROUND: Malignant glomus tumors are exceedingly rare, however they can be locally aggressive and have the potential to metastasize. There is limited information available in the literature regarding treatment and outcomes, therefore we present a case series of 5 patients with glomus tumors with malignant features confined to the extremities that have presented to our tertiary sarcoma center within the last 20 years. This is the largest case series of its kind in the malignant glomus tumor literature, to our knowledge. METHODS: We performed a retrospective chart review of all patients with histologically confirmed glomus tumors with malignant features in the extremities found within the University of Michigan EMERSE database since January 1st, 2000. RESULTS: Five patients met our inclusion and exclusion criteria. Three patients were diagnosed with malignant glomus tumors, one patient with glomus tumor with uncertain malignant potential, and the last patient with malignant glomus tumor with leiomyosarcomatous features. Males and females were equally represented. Age range was 9–49 years at time of first presentation. All patients underwent an initial surgical resection. Three of the five patients (60%) underwent initial resection at an outside hospital prior to referral to tertiary sarcoma center, and all three required re-resection. One of these patients had local tumor recurrence after a planned positive margin resection and radiotherapy. Another patient had distant metastasis after a positive margin surgical resection and a short course of radiotherapy. All patients are still alive according to their medical record with the average time from initial treatment to last follow up of 59.2 months. CONCLUSIONS: Our study supports the current literature that wide-local resection with the goal of negative margins is still the current gold standard treatment for glomus tumors with malignant features. Studies with larger cohorts are necessary before recommending for or against radiotherapy or chemotherapy. Early biopsy and referral to a tertiary sarcoma center prior to surgical resection may help reduce the re-resection rate and potential seeding of the tumor in these patients, thereby improving outcomes.